Pride and prejudice: gay rights and religious moderation in Belfast. (December 2013) - Curtis, Jennifer
Abstract: In the summer of 2008, a Northern Irish politician began publicly denouncing homosexuality. Her remarks galvanized responses from a broad range of groups and individuals. New voices joined the discussion of LGBT (lesbian, gay, bisexual and transgender) civil rights, including trade unions and political parties that had previously been silent. Notably, some Christian churches expressed their support for gay rights by participating in Belfast's annual LGBT Pride Festival. Since 2008, long‐standing opponents of gay rights have modulated their critiques. This article draws upon ethnographic research with Belfast's Pride Festival to examine religious groups' increasing support for LGBT rights since 2008. I describe this engagement as a practice of moderation in terms of its social and political effects. Here, moderation is conceived not in spatial terms as a position between opposed poles, but as a discursive practice that transforms political and religious debates. Drawing from Bakhtin's (1981) concept of 'dialogism', I consider how these discussions of Christianity, sexuality and politics unfolded. A Bakhtinian approach to the production and reception of these debates reveals how moderation is socially and historically situated. Moderation is practised in relation to particular conditions and histories, yet has the potential to transform them.